Pengaruh Practice Based Simulation Model Terhadap Peningkatan Psikomotor dan Self Efficacy - Achmad Vindo Galaresa; Elfiza Fitriami (Institut Citra Internasional, 2022)
Patient Simulation that can play a significant role or High Fidelity Simulation (HFS) has not been widely applied in Indonesia. A practice-based simulation model (PBSM) is an alternative to HFS because it can affect skill performance and self-efficacy. The purpose of this study was to analyze the effect of PBSM on the psychomotor and self-efficacy of nursing students in the nursing skill laboratory. The study used a quantitative method (Quasy Experiment), with a pretest-posttest approach without a control group. The population of this study was students at STIKes PMC Pekanbaru. Sampling using nonprobability sampling technique with 32 respondents and data analysis using Wilcoxon. PBSM affects psychomotor and self-efficacy (p) 0.000 <0.05, the ability to think consciously has a relatively limited capacity in the brain so it needs to be trained with various scientific approaches and PBSM is proven to be effective in increasing psychomotor and self-efficacy. PBSM has the advantage of increasing students' psychomotor and self-efficacy, but it is necessary to do a further in-depth study of the PBSM method with a more different method, duration of time, and measurement technique.